PENGARUH STRUKTUR KEPEMILIKAN MANAJERIAL DAN ARUS KAS TERHADAP NILAI PERUSAHAAN DENGAN DIVIDEN PAYOUT SEBAGAI VARIABEL MEDIASI (STUDY PADA PERUSAHAAN LQ45) - Muslimah, Kamalia; Hasan, Amir; Savitri, Enni (Jurnal Tepak Manajemen Bisnis, 2018)
This study aims to determine and analyze empirically the influence ofManagerial Ownership Structure and Free Cash Flow to Corporate Value. TheEffect of Payout Dividend on Corporate Value. the influence of Dividend Payoutis able to mediate the Managerial Ownership Structure of Corporate Values. Andthe influence of Dividend Payout is able to mediate Free Cash Flow againstCorporate Value. Population in this research is population in this research isPopulation selected in this research is company Company LQ45 at IndonesiaStock Exchange which exist in Bursa Efek Indonesia (BEI) as many as 27company. Data analysis using path analysis. The results of this study indicateManagerial Ownership Structure and Free cash flow significantly influence thevalue of the company. Deviden Pay Out Ratio has significant effect to companyvalue. Managerial Ownership Structure effect on firm value through Deviden PayOut Ratio. Free cash flow has an effect on company value through Deviden PayOut Ratio as intervening variable.